The Relationship Between Breastfeeding, Nutritional Status, and Exclusive Breastfeeding History with Stunting - Danefi, Tupriliany; Fenty Agustini; Anik Purwanti; Irfa Nurfajiah (Genius Journal, 2024)
Introduction: Stunting remains a nutritional problem facing Indonesia. The nutritional intake of breastfeeding mothers is closely linked to the production of breast milk, which is also a key factor in ensuring the adequate nourishment of infants and toddlers. Objective: The research aims to determine the relationship between the nutritional status of breastfeeding mothers, the history of exclusive breastfeeding, and the incidence of stunting in infants under five in Cikunir Village. Method: The type of research used is quantitative with analytical methods which aims to determine the relationship between the nutritional status of breastfeeding mothers, the history of exclusive breastfeeding, and the incidence of stunting in babies under five. The population is mothers who have babies aged 6-24 months in Cikunir Village, the sampling technique used purposive samples, samples were 52, the data presentation method was in tabular form, the analysis used descriptive and analytical analysis, the instrument used a questionnaire consisting of questions regarding the nutritional status of breastfeeding mothers, factors which affect nutritional status, history of exclusive breastfeeding, incidence of stunting. Result: The results of the statistical test on the relationship between the nutritional status of breastfeeding mothers and the incidence of stunting obtained a p-value of 0.307, so that 0.307 > alpha (0.05), while the results of the statistical test of the relationship between exclusive breastfeeding and the incidence of stunting obtained a p-value of 0.020 so that it was 0.020 < alpha. (0.05). Conclusion: There is no relationship between the nutritional status of breastfeeding and the incidence of stunting, and there is a relationship between exclusive breastfeeding and the incidence of stunting. The researcher postulates that if the nutritional status during pregnancy and breastfeeding is normal, yet the mother is ignorant, unable, or unwilling to obtain information about the nutrition that must be met during this period, this will result in stunting of the child. The prevention of stunting should commence with the provision of education and integrated services for pregnant women and mothers with children up to the age of two.